ACCRUAL AND REAL EARNINGS MANAGEMENT: ONE OF THE PERSPECTIVES OF PROSPECT THEORY - Imam Subekti (Universitas Hayam Wuruk Perbanas, 2012)
Earning management has become the practice in business. Yet, not all of the companies dothis earning management. The study aims to investigate earnings management behaviormeasured by real and accruals transactions i.e. abnormal cash flow of operation, abnormalproduction cost, abnormal discretionary, short-term discretionary accruals, and long-termdiscretionary accruals. The study applies a perspective of prospect theory to predict earningsmanagement behavior of management. In prospect theory, it is predicted that managers tendto manage earnings to avoid negative earnings. Positive earnings around zero is an indicationof earnings managed to avoid negative earnings. It shows that most of Indonesian publiccompanies tend to manage earnings based on real transactions than accruals transactions.All proxies of real earnings management support hypotheses that positive earnings aroundzero are managed through the real transactions. On contrary, only long-term discretionaryaccruals which support hypothesis revealing that positive earnings around zero is managedthrough accruals accounts. This result indicates that the Indonesian public companies engagein earnings management in accordance with the predictions of prospect theory, especiallythose based on real transactions.